FIRM REPUTATION UNDER PRESSURE: ESG CONTROVERSIES, BOARD GOVERNANCE, AND THE MODERATING ROLE OF ESG PERFORMANCE IN ASEAN-5 - Zulfani, Anisa; Solikhah, Badingatus (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This study aims to analyze the impact of ESG controversies, board independence, and gender diversity on corporate reputation in the ASEAN-5 region, as well as to evaluate the moderating role of ESG performance in this relationship. This study uses 2,896 observations of non-financial companies during the period 2020–2024 and applies panel data regression with the Fixed Effects Model and PCSE. The results show that ESG controversies have a significant negative effect on corporate reputation, board independence has a significant positive effect, while gender diversity has a significant negative effect. The moderation analysis indicates that ESG performance mitigates the negative impact of ESG controversies, weakens the positive influence of board independence, and strengthens the relationship between gender diversity and corporate reputation. Robustness tests confirm the consistency of the results. Overall, these findings show that the influence of board characteristics and ESG controversies on corporate reputation is affected by the level of ESG performance.